Farm to Table Meteorites: An End to End Exploration of the Solar System’s Past, Present, and Future. - Anderson, Seamus Lon (Curtin University, 2023)
Using Drones and machine learning to recover observed meteorite falls, analysis of extra terrestrial samples, and the future of space mining.